2019
DOI: 10.1007/s00125-019-4850-0
|View full text |Cite
|
Sign up to set email alerts
|

Continuous glucose monitoring in pregnant women with type 1 diabetes: an observational cohort study of 186 pregnancies

Abstract: Aims/hypothesis The aim of this study was to analyse patterns of continuous glucose monitoring (CGM) data for associations with large for gestational age (LGA) infants and an adverse neonatal composite outcome (NCO) in pregnancies in women with type 1 diabetes. Methods This was an observational cohort study of 186 pregnant women with type 1 diabetes in Sweden. The interstitial glucose readings from 92 real-time (rt) CGM and 94 intermittently viewed (i) CGM devices were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
171
3
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(192 citation statements)
references
References 45 publications
14
171
3
4
Order By: Relevance
“…The standard CGM metrics readily showed significant differences when it came to LGA, with a higher mean glucose at 24 and 34 weeks gestation; significantly lower time spent in pregnancy target range in each trimester, significantly higher time spent above the pregnancy target range of 3.5-7.8 mmol/l (63-140mg/dL) throughout pregnancy; and greater glucose variability in the first and second trimesters in those women who went on to have an LGA infant. This is consistent with the recent findings of an observational study of 186 pregnant women with type 1 diabetes using CGM in Sweden which showed that higher mean CGM glucose levels in the second and third trimester were significantly associated with LGA, as well as less time spent in pregnancy target range, and greater SD in second trimester (19).…”
Section: Discussionsupporting
confidence: 92%
“…The standard CGM metrics readily showed significant differences when it came to LGA, with a higher mean glucose at 24 and 34 weeks gestation; significantly lower time spent in pregnancy target range in each trimester, significantly higher time spent above the pregnancy target range of 3.5-7.8 mmol/l (63-140mg/dL) throughout pregnancy; and greater glucose variability in the first and second trimesters in those women who went on to have an LGA infant. This is consistent with the recent findings of an observational study of 186 pregnant women with type 1 diabetes using CGM in Sweden which showed that higher mean CGM glucose levels in the second and third trimester were significantly associated with LGA, as well as less time spent in pregnancy target range, and greater SD in second trimester (19).…”
Section: Discussionsupporting
confidence: 92%
“…In a commentary of this study, Helen Murphy suggests that for optimal obstetric and neonatal outcomes, women should aim to reach a TIR > 70% and a time above range < 25%, as early as possible during pregnancy. Those who can't achieve this target should be encouraged that any 5% increase in TIR is associated with clinically relevant improvements in neonatal health [25]. "…”
Section: Main Textmentioning
confidence: 99%
“…In the recent, “Recommendations from the International Consensus on Time in Range (TIR),” the lower glucose target threshold suggested during pregnancy is 3.5 mmol/L (63 mg/dL) 91 . Based on data from Sweden and the Continuous Glucose Monitoring in Women with Type 1 Diabetes in Pregnancy Trial (CONCEPTT), the TBR <3.5 mmol/L (<63 mg/dL) recommended is <4% of readings 127, 128 . However, the evidence on CGM metrics and targets, including TBR, for women with T2DM and gestational diabetes mellitus, is lacking.…”
Section: Hypoglycaemia During Pregnancymentioning
confidence: 99%